Will booster doses be required for serogroup B meningococcal vaccine? - McQuaid, F; Snape, MD (2014)
The European licensure of 4CMenB, the first vaccine licensed to prevent non-epidemic meningococcal B (MenB) disease, marked an important milestone in the fight against meningococcal disease. However, the potential introduction of 4CMenB into the routine infant schedule is complicated by a number of factors. The recent decline in the number of cases of invasive MenB disease in the UK has important implications for cost effectiveness, though the unpredictable nature of meningococcal disease epidemiology (as evidenced by a recent outbreak in MenB disease at Princeton University) means that it is not clear whether this decline will be sustained. The variable waning of antibody levels against each of the four key vaccine components also complicates the assessment of the likely duration and breadth of protection. After considering these factors, the UK Joint Committee on Vaccination and Immunisation (JCVI) released an interim statement in July 2013 indicating that the introduction of 4CMenB to the routine infant schedule was unlikely to be cost effective but highlighted the need for further data on strain coverage and persistence of immunity. This brief editorial discusses the possible role that booster doses of 4CMenB may have in prolonging persistence of immunity.